Knowledge, attitude and practice of prescribing antioxidants in patients with hypertension amongst practicing physicians - Vakharia, Monali Pradeep; Zad, Vijay Ramkrishna; Mankar, Nishikant Nandlal; Wadivkar, Pratik Pradeep (International Journal of Basic & Clinical Pharmacology, 2017)
Background: By altering the balance in the vascular endothelium between vasoconstrictors such as thromboxane and vasodilators such as nitric oxide, reactive oxygen species contribute to endothelium-dependent vasoconstriction and increased vascular resistance which is an important contributor to the pathogenesis of hypertension. Supplementation with antioxidants, including vitamin C, E, or B6, thiols such as lipoic acid and cysteine, and the quinone enzyme Q10, have been shown to lower blood pressure in animal models and humans with essential hypertension. The objective of this study was to assess knowledge and attitude of practicing physicians regarding use of antioxidants in patients with hypertension and to assess prescribing practices of antioxidants amongst these physicians. Methods: It was a cross-sectional questionnaire based study conducted amongst general practitioners, physicians, cardiologists and diabetologists in Solapur from 1 October 2015 to 30 October 2015. A total of 30 doctors were interviewed using a predesigned validated questionnaire. Results: Out of 30 doctors questioned, 24 (80%) doctors were aware of the role of oxidative stress in hypertension and 70% of doctors believed in prescribing antioxidants and its positive results on blood pressure. Only 10 (33.33%) doctors were actually prescribing antioxidants. Conclusions: At present, antioxidant vitamins are the feasible treatments for oxidative stress in humans and should be used more frequently by doctors. It is crucial that we consider the implications of trial design and execution, and further investigation of cellular pro-and antioxidant mechanisms is critical.